2015
DOI: 10.1167/tvst.4.4.6
|View full text |Cite
|
Sign up to set email alerts
|

High Tech Aids Low Vision: A Review of Image Processing for the Visually Impaired

Abstract: Recent advances in digital image processing provide promising methods for maximizing the residual vision of the visually impaired. This paper seeks to introduce this field to the readership and describe its current state as found in the literature. A systematic search revealed 37 studies that measure the value of image processing techniques for subjects with low vision. The techniques used are categorized according to their effect and the principal findings are summarized. The majority of participants preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Low vision aids can be divided into two categories according to their function: those that translate visual information into alternative sensory information, such as sound or touch (sensory substitution); and those that adapt visual information to render it more visible to the user, for example through magnification 8 . Several external magnifying low visual aids, amplifying the image to be recognizable by perimacular receptive fields of the retina, are available on the market.Loss of field of vision, a short reading distance, the weight and large size of the aid are the most common problems associated with these aids 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Low vision aids can be divided into two categories according to their function: those that translate visual information into alternative sensory information, such as sound or touch (sensory substitution); and those that adapt visual information to render it more visible to the user, for example through magnification 8 . Several external magnifying low visual aids, amplifying the image to be recognizable by perimacular receptive fields of the retina, are available on the market.Loss of field of vision, a short reading distance, the weight and large size of the aid are the most common problems associated with these aids 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Electronic head‐mounted low vision aids (e‐LVAs) have experienced a technological step change over the last decade . A 2017 review of head‐mounted displays for people with low vision highlighted the advantages of such technology over conventional desk‐mounted or handheld sight aids .…”
Section: Introductionmentioning
confidence: 99%
“…Modern e‐LVAs can embed digital sight enhancement algorithms that have been proven effective in laboratory settings for decades . A 2015 review of 37 research papers highlighted the benefit of various image processing techniques for the visually impaired, albeit with inconsistent preferences between people . A more recent review of e‐LVAs illustrated existing strategies to sight enhancement and showed improvements in contrast sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…The total score varied from 0 to 10. lenses for magnification, such as electronic magnifiers, digital image processing tools, and optical character recognition. 7 Over the past 3 decades, although the demographics of patients with low vision have remained constant, the number of spectacle-mounted optical devices has declined in correspondence with a rise in availability of newer technologies and electronic devices. 8 Our results indicate that the OrCam is an effective lowvision aid that is simple to understand and easy to use.…”
mentioning
confidence: 99%